Comparison of Burning Mouth Syndrome Prevalence and its Related Factors between Menopausal and Non-Menopausal Women - Maryam Baharvand; Majid Eshghpour; Hamed Mortazavi; Zeynab Fallah (Mashhad University of Medical Sciences, 2013)
Introduction: Burning mouth syndrome (BMS) is defined as burning and pain in the oral mucosa usually without any clinical and laboratory findings. It has a negative effect on patients' quality of life and can be a significant health problem. The aim of this study was to identify major risk factors associated with BMS in menopausal and non-menopausal women at dental clinics of Gorgan, Iran. Methods: This cross-sectional study was performed on 450 elderly female patients attending Gorgan dental clinics, Iran. Questionnaires were completed for all the patients by the examiner. For those with burning mouth, intraoral examination was performed to make sure of lacking any clinical pathoses. In addition to descriptive statistics, t-student, Chi-square, Fisher exact test, Mann-Whitney U tests, and Logistic Regression were used for data analysis. Results: In total, 13.8% of patients (n=62) suffered from BMS. Level of education (OR=4.67) and menopause (OR=4.45) were found to be a as predictors of increased prevalence of BMS in women of 30 to 60 years of age. According to Logistic Regression analysis, educational level, menstrual status, antidepressants, and systemic disease were significantly related to BMS. Conclusion: The prevalence of BMS among women in Gorgan (Iran) was relatively high, and the major risk factors were high level of education and menopause.